Usefulness of zebrafish larvae to evaluate drug-induced functional and morphological renal tubular alterations - Gorgulho, R. (2018)
Prediction and management of drug-induced renal injury (DIRI) rely on the knowledge of the mechanisms of drug insult and on the availability of appropriate animal models to explore it. Zebrafish (Danio rerio) offers unique advantages for assessing DIRI because the larval pronephric kidney has a high homology with its human counterpart and it is fully mature at 3.5 days post-fertilization. Herein, we aimed to evaluate the usefulness of zebrafish larvae as a model of renal tubular toxicity through a comprehensive analysis of the renal alterations induced by the lethal concentrations for 10% of the larvae for gentamicin, paracetamol and tenofovir. We evaluated drug metabolic profile by mass spectrometry, renal function with the inulin clearance assay, the 3D morphology of the proximal convoluted tubule by two-photon microscopy and the ultrastructure of proximal convoluted tubule mitochondria by transmission electron microscopy. Paracetamol was metabolized by conjugation and oxidation with further detoxification with glutathione. Renal clearance was reduced with gentamicin and paracetamol. Proximal tubules were enlarged with paracetamol and tenofovir. All drugs induced mitochondrial alterations including dysmorphic shapes (“donuts”, “pancakes” and “rods”), mitochondrial swelling, cristae disruption and/or loss of matrix granules. These results are in agreement with the tubular effects of gentamicin, paracetamol and tenofovir in man and demonstrate that zebrafish larvae might be a good model to assess functional and structural damage associated with DIRI. © 2017 Springer-Verlag GmbH Germany